Spatial and temporal distribution patterns of Anopheles arabiensis breeding sites in La Reunion Island - multi-year trend analysis of historical records from 1996-2009 - Lempérière Guy; Boyer Sebastien; Girod Romain; Dehecq Jean-Sébastien; Gouagna Louis C; Fontenille Didier (Parasites & Vectors, 2011)
Abstract Background An often confounding facet of the dynamics of malaria vectors is the aquatic larval habitat availability and suitable conditions under which they can thrive. Here, we investigated the impact of environmental factors on the temporal and spatial distribution of larval habitats of Anopheles arabiensis in different locations on La Reunion Island. Methods A retrospective examination was made from archival data which provided the complete enumeration of An. arabiensis breeding habitats in three distinct geographic zones - extending North-east, West and South of the island over 14 years, from January 1996 to December 2009. Data on the occurrence and the number of active larval habitats at each of a total of 4376 adjacent ellipsoid grid cells (216,506 square meters each) were used (1) to provide the geographic extent of breeding site availability from year to year and (2) to analyze associations with prevailing environmental factors, habitat types, and locations. Results Anopheles arabiensis utilized a spectrum of man-made and natural aquatic habitats, most of which were concentrated primarily in the rock pools located in ravines and river fringes, and also in the large littoral marshes and within the irrigated agricultural zones. The numbers of breeding site per sampling grid differed significantly in different parts of the island. In contrast to an originally more widespread distribution across the island in the 1950s, detailed geographic analyses of the data obtained in the period extending from 1996-2009 showed an intriguing clustered distribution of active breeding sites in three discontinuous geographic zones, in which aquatic habitats availability fluctuates with the season and year. Seasonality in the prevalence of anopheles breeding sites suggests significant responsiveness to climatic factors. Conclusions The observed retreat of An. arabiensis distribution range to lower altitudinal zones (< 400 m) and the upward shift in the most remote littoral areas in the northeast and southwest regions suggest the possible influence of biogeographic factors, changes in land use and control operations. The results of this study would allow for a more rational implementation of control strategies across the island.